Enciclopedia dei Papi, Roma, Istituto della Enciclopedia Italiana Treccani, 3v., 746 pp., 717 pp. y 741 pp - Hubeñak, Florencio (2005)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina; Argentina